Relating fitness phenotypes to genotypes in Lithuanian elite athletes - GINEVIČIENĖ, Valentina; PRANCKEVIČIENĖ, Erinija; MILAŠIUS, Kazys; KUČINSKAS, Vaidutis (Acta medica Lituanica, 2010)
Background. We aim to link fitness-related genotypes to the development of specific physical fitness phenotypes and a predisposition towards a specific sport category in Lithuanian elite athletes. Materials and methods. The study involved 193 athletes (152 male and 41 female) and 250 controls. The athletes were stratified into four groups: endurance, mixed sports, speed / power, and team sports. Genotypes of the athletes were identified according to the genetic polymorphisms: ACE (rs1799752), ACTN3 (rs1815739), PPARGC1A (rs8192678) and PPARA (rs4253778). One-way analysis of variance and logistic regression modelling were used for testing the genotype–phenotype association. Results. The frequency of ACE I allele was higher in athletes than in controls, although only male athletes showed a significant difference from male controls. The PPARA C allele was more common in the athlete group than in the general population of Lithuania. There were no significant ACTN3 and PPARGC1A SNP allele / genotype frequency differences between the athlete group and the controls. We have found that the ACTN3 RR genotype is associated with single muscular contraction power; the PPARGC1A Ser482Ser was associated with the muscle fat mass index; the PPARA CC and ACE II genotypes are associated with the muscle mass and single muscular contraction power. The effect of the gene variants was different for male and female athletes. Conclusions. The ACE II, PPARA CC, ACTN3 RR genotypes are related to the speed/power sports and the ACE DD, PPARA GG are related to the endurance sports in Lithuanian athletes. PPARGC1A Ser482Ser may be not critical but rather additive to endurance performance. Keywords: physical performance, ACE, ACTN3, PPARGC1A and PPARA genetic variants, sport category